Sensory Characteristics of Walnut Fish Balls Made from Sago Flour Filler - Mailoa, Meitycorfrida; Tulalessy , Abraham H. (The Islamic Education and Multiculturalism Foundation, 2023)
Meatballs are a type of food that is very well known and liked by the wider community ranging from children to adults. Meatballs made from skipjack tuna (Katsuwonus pelamis) have not been found in the market, even though skipjack tuna in Maluku is one of the potential commodities. Skipjack tuna contains 19.6 g of protein and is very beneficial for the growth of children. The use of local food to process it into one nutritious food product is very important, meaning reducing dependence on food imported from outside the region. In addition to skipjack tuna, walnuts are also one of the local foods with high protein content (12.1%), so these two local foods from Maluku have been fortified into meatballs By using several formulation treatments, namely the ratio of fish to walnuts in percent (100: 0; 80: 20; 60: 40; 40: 60 and 20: 80). This study aims to determine the best formulation of meatballs from fish and walnut base ingredients and made from sago flour filler. The benefit of this study is that consumers can consume the meatballs produced, especially for stunted children who experience protein nutrition deficiencies. The experimental design used was a Factorial Complete Randomized Design using 5 treatments, namely skipjack tuna: walnut (%): (100: 0; 80: 20; 60: 40; 40: 60; 20: 80) with two replays So that 10 experimental units were obtained. The data is sensorily analyzed to determine its characteristics including hedonic tests (very like, like, somewhat like, and dislike) of taste, aroma, chewiness/texture, and color as well as quality tests hedonistic to the texture (very chewy, chewy, slightly chewy and not chewy) as well as flavor (very savory, savory, somewhat savory and not savory). Sensory tests were conducted on 30 somewhat trained and trained panelists. The data were analyzed in a fingerprinted manner and if there was a noticeable difference, it was followed by the Tukey test with a 95% confidence level.